Analisis Faktor-Faktor Penyebab Siswa Putus Sekolah di SMP Negeri 1 Lemito - Irwilda H. Bay (Lembaga Pengembangan Kinerja Dosen, 2026)
SMP N 1 Lemito is a school that has been operating since 1984. This school is considered as the first step for children in Lemito District to achieve various dreams. However, in reality, there are still students who choose to drop out of school due to various problems every year. The purpose of this study is to analyze the factors that cause students at SMP N 1 Lemito to drop out of school. The method in this study uses a qualitative descriptive approach to gain an in-depth understanding of the reasons why students choose to drop out of school. Data collection was carried out through interviews, observations, and documentation. Meanwhile, the Miles and Huberman model, which includes data reduction, data presentation (data display), and conclusion drawing, was applied for data analysis. The results of this study explain that the cause of students at SMP N 1 Lemito dropping out of school is due to internal factors where problems arise from the students' own behavior which impacts a lack of enthusiasm and causes laziness during learning activities at school. Furthermore, it is known that there are several negative habits such as smoking, drinking alcohol, sniffing glue, and a culture of thuggery. Meanwhile, external factors originate from the influence of the family economy, low awareness of parents/guardians regarding children's education and the influence of the social environment outside of school which influences students' mindsets so that they feel uncomfortable in the school environment.